The missing link: Unifying risk taking and time discounting - Thomas Epper; Helga Fehr-Duda (University of Zurich, Department of Economics, 2012)
Almost all important decisions in people's lives entail risky and delayed consequences. Regardless of whether we make choices involving health, wealth, love or education, almost every choice involves costs and benefits that are uncertain and materialize over time. Because risk and delay often arise simultaneously, theories of decision making should be capable of explaining how behavior under risk and over time interacts. There is, in fact, a growing body of evidence indicating important interactions between behaviorally revealed risk tolerance and patience. Risk taking behavior is delay dependent, and time discounting is risk dependent. Here we show that the inherent uncertainty of future events conjointly with people's proneness to weight probabilities nonlinearly generates a unifying framework for explaining time-dependent risk taking, risk-dependent time discounting, preferences for late resolution of uncertainty, and several other puzzling interaction effects between risk and time.
Keywords: D01; D81; D91; 330; risk taking; time discounting; probability weighting; decreasing impatience; increasing risk tolerance; preference for late resolution of uncertainty; preference for one-shot resolution of uncertainty; Risikopräferenz; Zeitpräferenz; Entscheidung bei Unsicherheit; Theorie